Attitudes of Karak University College students towards distance learning during the Corona pandemic - Al-Majali, Ala’a A. (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed at identifying the level of students’ attitudes towards distance learning in light of the Corona pandemic and detecting differences in students’ attitudes towards the application of distance learning in light of the Corona pandemic. Methods: An intentional sample of students from Karak University College made up of 124 male and female students was chosen randomly. The study instrument was divided into two sections: a portion with personal information (gender, program, and level) and a section with paragraphs measuring the many aspects of distant learning. These 26 paragraphs were grouped into three categories: student, faculty member, and university. It was given to the study sample after the validity and reliability of the study tool had been established. Results: Students at Karak University College had average attitudes toward distance learning during the Corona epidemic, with faculty members having the best attitudes, universities coming in second with average attitudes, and students having the worst attitudes. Also, there are no gender-specific variations in how students feel about remote learning during the Corona pandemic. Also, due to the program in support of the academic diploma, there are disparities in how the students feel about remote learning during the Corona pandemic. There are distinctions based on level, favoring the second year. Conclusion: According to the study’s findings, attitudes among students were ordinary. The study made the case that distant learning should remain an accepted educational pattern in universities and not be used as a fallback or emergency replacement for in-person instruction.